1996
DOI: 10.1177/0146167296222005
|View full text |Cite
|
Sign up to set email alerts
|

Envy and Schadenfreude

Abstract: To test the hypothesis that Schadenfreude, pleasure at the suffering of others, will result when an envied person experiences a misfortune, envy was created in subjects by asking them to watch a videotaped interview of a student who was made to appear either superior or average. An epilogue informed subjects that the student had suffered a recent setback. The envy created in subjects was found to enhance the likelihood that they would feel Schadenfreude on learning of this setback. In addition, dispositional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
290
1
14

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(324 citation statements)
references
References 19 publications
10
290
1
14
Order By: Relevance
“…Although an examination of interpersonal emotion, R. H. Smith et al (1996) have shown schadenfreude to result from perceived inferiority in much the same way as Nietzsche suggested.…”
Section: The Threat Of Status Inferiority Should Increase Schadenfreudementioning
confidence: 90%
See 2 more Smart Citations
“…Although an examination of interpersonal emotion, R. H. Smith et al (1996) have shown schadenfreude to result from perceived inferiority in much the same way as Nietzsche suggested.…”
Section: The Threat Of Status Inferiority Should Increase Schadenfreudementioning
confidence: 90%
“…This is because greater interest in the domain increases the self-relevance of others' performance within the domain. Although focused on the interpersonal level, a number of emotion theories also propose that others' misfortunes in self-relevant domains promote schadenfreude (e.g., Lazarus, 1991;Ortony et al, 1988; R. H. Smith et al, 1996). Although not specifically concerned with intergroup schadenfreude, research in the social identity theory tradition is also consistent with this notion.…”
Section: Domain Interest Should Increase Schadenfreudementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Batson and colleagues (Batson, Eklund, Chermok, Hoyt, & Ortiz, 2007) suggested that perceived need, imagining the other's perspective, and valuing the other's welfare are antecedents of empathy. With regard to schadenfreude, research has shown that perceivers are more likely to experience schadenfreude if the misfortune is perceived as deserved (Feather & Sherman, 2002), if the misfortune is befalling an envied person (Smith, Turner, Garonzik, Leach, Urch-Druskat, & Weston, 1996), or if the person befalling the misfortune is disliked (Hareli & Weiner, 2002). It thus may be that playing prosocial video games increases the accessibility of prosocial thoughts, which in turn evokes one of these direct antecedents of empathy and schadenfreude.…”
Section: Implications Limitations and Future Researchmentioning
confidence: 99%
“…Social psychologists have suggested, in fact, that misfortunes of the wealthy can evoke a malicious pleasure in others, for people in general feel some satisfaction in the downfall of those far more successful than they themselves are (a phenomenon labeled schadenfreude; see Brigham, Kelso, Jackson, & Smith, 1997;Feather & Sherman, 2002;Smith, 2000;Smith et al, 1996).…”
Section: Judgments About Choices and Controlmentioning
confidence: 99%